The Influence of Quality Service Housekeeping Department on Customer Satisfaction at Maxone Hotel Platinum Hayam Wuruk Jakarta - Aditya Pratomo (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The purpose of the study is to know the high influence of service quality on customer satisfaction at hotel Maxone Platinum Hayam Wuruk Jakarta. It can see service quality affects the guest hotel. This study used a qualitative approach based on the questionnaire. The data collecting technique for the sample was based on purposive sampling, total 100 respondents. The result of this study is that service quality influences 83.6%. The resulting hypothesis of selling in quality service variable significant influence customer satisfaction.